2022
DOI: 10.3390/foods11162397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Washing Times on the Quality Characteristics and Protein Oxidation of Silver Carp Surimi

Abstract: The aim of this work is to evaluate the effects of different washing times (zero (W0), one (W1), two (W2), and three (W3) times) on the physicochemical characteristics, gel property, and protein oxidation of silver carp surimi during 4 °C refrigeration. The results showed that the yield, types of fatty acids, redness (a*), total volatile basic nitrogen, and thiobarbituric acid reactive substances of the surimi tended to decrease, and the whiteness, pH, gel strength, and water retention tended to increase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…FTIR can be used to obtain the amino groups in protein molecules, where the peaks from 1700 cm −1 to 1600 cm −1 correspond to the amide I band, representing the stretching vibration of C=O [31]. At present, the identification of amide I band peaks has been widely used, with 1651 cm −1 to 1660 cm −1 being α-Helix, 1610 cm −1 to 1640 cm −1 being β-Sheet, 1660 cm −1 to 1700 cm −1 being β-Turn, and 1640 cm −1 to 1650 cm −1 being Random [32].…”
Section: Effect Of Ftc On the Secondary Structure Of Protein In Focnmentioning
confidence: 99%
“…FTIR can be used to obtain the amino groups in protein molecules, where the peaks from 1700 cm −1 to 1600 cm −1 correspond to the amide I band, representing the stretching vibration of C=O [31]. At present, the identification of amide I band peaks has been widely used, with 1651 cm −1 to 1660 cm −1 being α-Helix, 1610 cm −1 to 1640 cm −1 being β-Sheet, 1660 cm −1 to 1700 cm −1 being β-Turn, and 1640 cm −1 to 1650 cm −1 being Random [32].…”
Section: Effect Of Ftc On the Secondary Structure Of Protein In Focnmentioning
confidence: 99%
“…This could have been due to the elements in the meat, such as dirt, fat, blood, and sarcoplasm dissolving in the water during the washing procedure with cold water at 10°C (5 -10). Zhang et al (2022) stated that washing can cause some of the immobilised water in fish to be transferred to free water, thus increasing the water's fluidity. The highest yield (68.50%) was obtained after three washes with 4% atung solution (A2B3).…”
Section: Objective Parameters Yieldmentioning
confidence: 99%
“…The number of washes directly affects the quality and economic benefits of surimi. By comparing different numbers of washes (0, 1, 2, 3), Zhang et al [7] found that the yield, types of fatty acids, redness (a*), total volatile basic nitrogen, and thiobarbituric acid-reactive substances of the surimi decreased, and the whiteness, pH, gel strength, and water retention increased, with increasing numbers of washes. They suggested that two washes was optimal, taking into account yield, water consumption, and surimi quality.…”
Section: Aquatic Product Processingmentioning
confidence: 99%